Transcriptomic reveals key genes and regulatory pathways in galactomannan biosynthesis in Gleditsia sinensis polysaccharide gum - Zhang, Yanyan; Yang, Tingting; Wang, Xiangpei; Xu, Feng; Du, Linlin; Wu, Hongmei (Frontiers in Plant Science, 2025)
IntroductionThe Gleditsia sinensis Lam. polysaccharide gum contained in G. sinensis seeds is not only an additive specified in national food standards, but also an important strategic resource for industrial raw materials such as oil and natural gas in China.The main component of G. sinensis polysaccharide gum is galactomannan (GM). To date, most studies have focused on the structural modification and component separation of the polysaccharide gum of G. sinensis seeds, with only a few reports on the regulatory genes involved in its formation.MethodsTranscriptome analysis was performed to assess the gene networks associated with GM synthesis in G. sinensis seeds at four stages: 6, 9, 12, and 16 weeks after flowering.ResultsThe result indicated that differential expression analysis identified 20 unigenes linked to five critical enzymes in the GM biosynthesis pathway. Further pathway enrichment analysis demonstrated that fructokinase, galactose gyrase, inositol galactoside synthase, phosphogalactosyltransferase, and raffinose synthase play pivotal roles in GM biosynthesis, positively regulating its production.DiscussionThe results of this study provide new ideas for the research of GM biosynthesis related genes in G. sinensis and enhance the potential application prospects in genetic engineering.